(untitled) (Dentika: Dental Journal, 2009)
Modelling wax is a pattern wax for complete denture fabrication. It consists of various waxes and other components. The composition influenced the physical properties of modelling wax. The objective of this study was to examine the effect of paraffn to beeswax ratio on the linear thermal expansion (LTE) of modelling wax. The modelling waxes consist of paraffin (Pertamina, Kalimantan), beeswax (SEA, Yogyakarta), carnauba wax (PT Bratachem, Indonesia), and dammar (Kalimantan). Five compositions of waxes were made with different paraffin to beeswax ratio (paraffin: beeswax: carnauba wax: dammar in % weight): K1 = 70:20:4:6, K2 = 72.5:17,5:4:6, K3 = 75:15:4:6, K4 = 77.5:12.5:4:6, and K5 = 80:10:4:6. Six specimens (305 x 22.2 x 14.3 mm) were made of each composition. The specimens were immersed in bathing water at 25Â°C and 40Â°C for 20 minutes, and the specimen length was measured by travelling microscope after each immersion. The percentage of the LTE was measured. Data were analyzed by one-way Anova and LSD0.05. The results showed that the LTE of modelling waxes was between 0.27 + 0.02 % (70:20 ratio) and 0.73 + 0.06 % (80:10 ratio). The Paraffin to beeswax ratio influenced the LTE of modelling waxes and showed the significant differences between all compositions (p<0.5). As conclusion, the paraffin to beeswax ratio influenced the linear thermal expansion of modelling wax.